Developmental origins of health and disease (DOHaD) and paternal origins of health and disease (POHaD). Multigenerational inheritance - O. V. Sergeyev; A. I. Nikitin (Акушерство, гинекология и репродукция)
This review addresses the concept of ontogenetic origin of health and disease (DOHaD) and the new concept of paternal origin of health and disease (POHaD). These concepts are based on scientific evidence that environmental factors impacting mother or father can play a role in reprogramming the health of their off springs throughout their life span. Moreover, the changes that have arisen can be transmitted through generations via diverse epigenetic mechanisms. Terms, such as epigenetics (a kind of “driver” for these concepts), epigenetic inheritance (including Intergenerational Inheritance – from generation to the next generation and Transgenerational Inheritance – through generations), epigenetic changes caused by the environment (Environmental Epigenetics) are discussed. Vulnerable periods towards epigenetic changes (Windows of Susceptibility) that occur in male germ cells responsible for epigenetic inheritance are considered. Epigenetic epidemiological studies in the field of reproductology are described; their advantages and disadvantages are discussed. These studies can serve as the basis for obtaining new knowledge about the causes of epigenetic variations in germ cells that occur in health and upon exposure to environmental factors as well as the inherited phenotypic outcomes.